Leksikon YU mitologije – the phenomena of Yugoslavian popular culture and their “second life” - Szczepański, Wojciech (Myths and Stereotypes in the Collective Representations, 2019)
For some time now Poles seem to be increasingly more interested in the Yugoslav popular culture which has thus been gaining its own experts as well as lovers in Poland. It is undoubtedly associated with the development of studies in fields such as (Southern) Slavonic and Balkan Philology as well as with increasing historical, politological, ethnological and anthropological research into the past and present of the post-Slavic area, including cultural, social and political issues.Leksikon YU mitologije (The Lexicon of YU mythology), published in 2005 in Serbian (Belgrade) and distributed more widely in Croatia, is a unique work in the field of cataloging and recognizing phenomena of popular culture of Yugoslavia. This impressive book edited by Iris Adrić, Vladimir Arsenijević and Djordje Matić several years after the break-up of the Socialist Federative Republic of Yugoslavia (SFRY) is the result of work of many professional lexicographers and even a larger group of amateur lexicographers representing different nationalities. It is also the realisation of a design of Dubravka Ugrešić, Dejan Kršić and Ivan Molek dating back to 1989, a few years before the fall of SFRY.The thoughts on some of the content contained in lexicon is to provide not only an opportunity to look at the selected phenomena of popular Yugoslav culture in the communist period. It is also intended as a contribution to reflection and discussion on the relationship of these phenomena with the identity of the Yugoslavs over their current functioning, hence “life after life”), and finally on the determinants of the process of the creation of certain specific images of collective memory, among which one should mention “yugonostalgia”, which is one of the most important imperatives of participation of many authors of the lexicon.